Molecular pathways linking chronic psychological stress to accelerated aging: mechanisms and interventions - Alhazzaa, Othman A.; Abahussin, Hanin M.; Majrashi, Majed A.; Alotaibi, Maryam S.; Alkhrayef, Mohammad N.; Alhamdan, Ziyad A.; Alawad, Abdullah O. (Frontiers in Aging, 2026)
Chronic psychological stress refers to repeated or prolonged exposure to adverse social or emotional threats that exceed an individual’s adaptive capacity. It is recognized as a risk factor for aging-associated diseases. A growing body of research has shown that there is a link between chronic psychological stress and accelerated aging. Here, we highlight recent findings on the interconnected relationship between chronic psychological stress and major aging hallmarks, including mitochondrial dysfunction, telomere attrition, cellular senescence, epigenetic alterations, inflammation, and genomic instability. We discuss the mechanisms by which chronic psychological stress may drive this effect and explore intervention strategies that could mitigate its adverse effects and promote healthy aging. Moreover, we address current research gaps and propose future research directions to improve our understanding of the intricate relationship between psychological stress and aging.